Kebakaran Pasar Horas Pematang Siantar : Dampak pada Komunitas Pedagang dan Strategi Pemulihan - Rafi Ramadhan Lubis; Felisa Jauzarafa; Arya Pranata Sidabutar; Berlianti Berlianti (Institut Nalanda, 2024)
Fire is one of the disasters that can cause great losses, both in terms of material and social. This study aims to analyze the causes, impacts, and efforts to overcome fire disasters that occur in Horas Tax, Pematang Siantar. This study uses a descriptive qualitative method with data collection through interviews, field observations, and document analysis. The results showed that the fire at Pajak Horas was caused by an electrical short circuit that was exacerbated by a less than optimal market governance system, such as the lack of fire prevention facilities and infrastructure conditions that did not meet safety standards. The impacts include economic losses for traders, disruption of social activities, and damage to market infrastructure. Mitigation efforts involve cooperation between the local government, firefighters, and the community, including increased education on fire hazards, provision of fire extinguishers, and market reorganization. This study recommends the need to strengthen regulations and implement disaster risk management in traditional market areas to minimize similar events in the future.